Remifentanil, Isoflurane, and Preconditioning Attenuate Renal Ischemia/Reperfusion Injury in Rats - Vianna, Pedro Thadeu Galvão [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Viero, Rosa Marlene [UNESP]; Beier, S.; Vianna Filho, P. T. G.; Vitoria, A.; Bizarria Guilherme, G. Reinoldes; Golim, Márjorie de Assis [UNESP]; Deffune, Elenice [UNESP] (Elsevier B.V., 2009)
Background: The purpose of this investigation was to examine the effect of isoflurane, remifentanil, and preconditioning in renal ischemia/reperfusion injury (IRI).Methods: M 52 male Wistar rats were anesthetized with isoflurane, intubated and mechanically ventilated. The animals were randomly divided into: S group (sham; n = 11) that underwent only right nephrectomy; as well as the I group of right nephrectomy and ischemia for 45 minutes by clamping of left renal artery. (n = 11); the IP (n = 9), the R (n = 10), and the RP (n = 11) groups. In addition, the R and RP animals received remifentanil (2 mu g.kg(-1).min(-1)) during the entire experiment. The IP and RP group underwent ischemic preconditioning (IPC = three cycles of 5 minutes). Serum creatinine values were determined before and after IRI, as well as 24 hours later. In addition to an Histological study, cells from the left kidney were evaluated for apoptosis by flow cytometry (FCM).Results: The Creatinine value of 0.8 +/- 0.2 mg/dl in the S group was significantly lower at 24 hours than the 13.9 +/- 1.5 mg/dl; IP 2.6 +/- 1.7 mg/dl; R 3.3 +/- 2.8 mg/dl; or RP 1.8 +/- 0.5 mg/dl groups. The RP group value was significantly lower than those of the I, IP, and R groups (p < 0.05). The S group showed less proximal tubular cell damage than the 1, IP, R, and RP groups (p < 0.05). The percentages of apoptotic cells (FITC+/PI-) were: S group = 11.6 +/- 6.5; I = 16.7 +/- 7.3; IP = 37.0 +/- 28.4; R = 11.7 +/- 6.6, and RP = 8.8 +/- 1.5. The difference between the IP vs RP group was significant. Similar percentages of necrotic cells (FITC+/PI+) and intact cells (FITC-/PI-) were observed among the groups.Conclusions: Ischemic preconditioning showed no protective effect in the isoflurane group (IP) but when isoflurane was administered associated with remifentanil (RP), there was a beneficial effect on the kidney, as demonstrated by flow cytometry and serum creatinine values.